Changing Education
XII, 350 p.
Keywords: This book responds to the growing unease of educators and non-educators alike about the inadequacy of most current educational systems and programs to meet sufficiently the demands of fast changing societies. These systems and programs evolved and were developed in and for societies that have long been transformed, and yet no parallel transformation has taken place in the education systems they spawned. In the last twenty years or so, other sectors of society, such as transportation and communications systems, have radically changed the way they operate, but education has remained essentially the same. There is no doubt: education needs to change. To those ready to accept this challenge, this book represents a welcome guide. Unlike most books on educational policy, this volume does not focus on improving existing educational systems but on changing them altogether. Its focus is not on doing things better, but on doing better things; not on doing things right, but on doing the right things to prepare students for a fast changing interdependent world.